Quality versus quantity: response of riparian bird communities to aquatic insect emergence in agro-ecosystems - Rideout, Natalie K.; Alavi, Niloofar; Lapen, David R.; Hajibabaei, Mehrdad; Mitchell, Greg W.; Monk, Wendy A.; Warren, Marlena; Wilson, Scott; Wright, Michael T. G.; Baird, Donald J. (Frontiers in Sustainable Food Systems, 2025)
In many agricultural landscapes where field drainage is required to enhance crop production, agricultural drainage ditches, and their associated banks and hedgerows can support riparian biodiversity, including bird communities. Against a global background of farmland bird and terrestrial insect decline due to agricultural intensification and extensification, emerging aquatic insects in these aquatic corridors can provide a pulse of energy-rich, nutritionally-important food for birds and other wildlife. In this paper, we quantify the value of drainage ditch habitats in terms of aquatic insect production as a potential food source for riparian foraging birds in a river basin in eastern Canada. Despite being highly managed, agricultural drainage ditches remained extremely productive in terms of emerging biomass of aquatic insects (high quantity), but large-bodied aquatic insects such as mayflies, stoneflies and caddisflies, which are rich in fatty acids, were more common in natural, forested streams and less common in agricultural streams and ditches. The proportion of riparian insectivorous birds was lowest along straight ditches running through agricultural fields and highest among meandering (sinuous) streams in more forested areas, suggesting that agricultural drainage systems may not be able to fully support resource use for foraging predators that rely on emerging aquatic insects. Agricultural producers can improve habitat provisioning for birds on their farms by supporting mosaicked farmscapes through careful conservation and management of ditches and ditch bank vegetation. Establishing larger forest blocks with natural or unmanaged streams between areas of more intense land use can ensure the provisioning of more high quality prey to riparian insectivorous birds, helping to find the balance between agricultural productivity and protection of declining bird populations.